2015
DOI: 10.1159/000379753
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Attenuates NMDA-Induced Damage to Rat's Retinal Ganglion Cells in an Age-Dependent Manner

Abstract: Objective: This study was conducted to investigate neuroprotective effects of a high fat/low carbohydrate and protein diet (ketogenic diet, KD) in a model of N-methyl D-aspartate (NMDA)-induced retinal ganglion cell (RGC) damage in juvenile and young adult rats. Methods: Juvenile (30-35 days old) and young adult (56-70 days old) female Brown Norway rats were fed the KD for 21 days; rats exposed to a standard rodent diet (SRD) served as controls. The main constituents of the KD used in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Changes in the beneficial effect of CR (Li et al., 2003) or ketogenic diet (Zarnowski et al., 2015) have been reported based on the age at onset of these diets. In addition, ketone oxidation declines in an age‐dependent manner due to decrease in metabolic enzyme activity (Bregere, Rebrin, Gallaher, & Sohal, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the beneficial effect of CR (Li et al., 2003) or ketogenic diet (Zarnowski et al., 2015) have been reported based on the age at onset of these diets. In addition, ketone oxidation declines in an age‐dependent manner due to decrease in metabolic enzyme activity (Bregere, Rebrin, Gallaher, & Sohal, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…CR attenuates the decrease in RGC activity caused by intraocular pressure elevation (Kong et al., 2012) and protects against ischemia/reperfusion stress‐induced RGC reduction (Kawai et al., 2001). A ketogenic diet and high‐fat/low‐carbohydrate and protein diet cause the elevation of endogenous 3HB and attenuate age‐related damage to RGC in rats (Zarnowski et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However, KD effects on mitochondria were not analyzed in any of these patients. On the other hand, KD has not been used in LHON patients, but LHON patients suffer from RGC loss and, in rodent models of RGC damage, it was shown that KD have a RGC neuroprotective effect, preserving its structure and function, increasing mitochondrial respiration and up-regulating mitochondrial biogenesis [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…There is a precedent to suggest that ketone metabolism plays an important role in retinal homeostasis. [13][14][15] In the retinal pigment epithelium (RPE), degraded lipids from the shed photoreceptor outer segments are metabolized via β-oxidation to generate acetyl CoA, an important source of energy. 14,15 Furthermore, the RPE converts acetyl CoA into the ketone, β-hydroxybutyrate (BHB), which can be shuttled back to the photoreceptors and used as an additional energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that a ketogenic diet with approximately 80% fats, 8% proteins, and <1% carbohydrates protected retinal ganglion cells from N-methyl D-aspartate-induced damage. 13 We hypothesized that inducing ketosis through ketogenic diet administration would elicit neuroprotection of photoreceptors. To test this hypothesis, we evaluated two different ketogenic diets in rd10 mice, a relevant and well-characterized genetic model of RP.…”
Section: Introductionmentioning
confidence: 99%